2018
DOI: 10.1103/physreve.98.062312
|View full text |Cite
|
Sign up to set email alerts
|

Feedback through graph motifs relates structure and function in complex networks

Abstract: In physics, biology and engineering, network systems abound. How does the connectivity of a network system combine with the behavior of its individual components to determine its collective function? We approach this question for networks with linear time-invariant dynamics by relating internal network feedbacks to the statistical prevalence of connectivity motifs, a set of surprisingly simple and local statistics of connectivity. This results in a reduced order model of the network input-output dynamics in te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…The imaging data used throughout this manuscript was described in a previous study [4]. Briefly, the activity of L2/3 excitatory neurons expressing GCaMP6s in mouse visual cortex (73-347 neurons; n = 8 animals; 21 distinct fields of view; Fig 1A) were imaged using two photon laser scanning microscopy (25)(26)(27)(28)(29)(30)(31)(32)(33) Hz; [4,33]). Mice were awake and allowed to freely run on a linear treadmill while viewing drifting square-wave gratings presented in 12 directions in pseudo-random order interleaved with mean-luminance matched grey screen; each trial was a 5-minute block of stimulus presentation in this format.…”
Section: Mouse Visual Cortical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The imaging data used throughout this manuscript was described in a previous study [4]. Briefly, the activity of L2/3 excitatory neurons expressing GCaMP6s in mouse visual cortex (73-347 neurons; n = 8 animals; 21 distinct fields of view; Fig 1A) were imaged using two photon laser scanning microscopy (25)(26)(27)(28)(29)(30)(31)(32)(33) Hz; [4,33]). Mice were awake and allowed to freely run on a linear treadmill while viewing drifting square-wave gratings presented in 12 directions in pseudo-random order interleaved with mean-luminance matched grey screen; each trial was a 5-minute block of stimulus presentation in this format.…”
Section: Mouse Visual Cortical Datamentioning
confidence: 99%
“…In visual cortex, visually tuned neurons with similar stimulus selectivity are more likely to be synaptically interconnected [25] and these connections manifest as specific motifs [24] which coordinate synaptic integration [26]. Moreover, populations of neurons have been shown to exhibit higherorder state correlations [23,27], and topological network features have been shown to shape spike propagation and information transfer [26,28,29]. However, the relative role of local synaptic connectivity, as compared to stimulus-related input or more global variables such as locomotion, in the generation of a sensory representation, particularly in real time, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…390 The necessity of higher-order patterns for stable activity has strong implications for 391 neural coding. Previous work has already demonstrated that correlations enhance 392 coding, with triplet correlations having an advantage over pairwise 393 [5,16,18,[21][22][23][52][53][54]. The neural code must rest upon a foundation of stable 394 propagation of spikes, which we have shown in turn rests on higher-order motifs and 395 coordinated integration.…”
mentioning
confidence: 77%
“…These abstract metrics facilitate comparison of the structure of di-verse neural populations. For example, Hu et al (2016) proposed a method to relate the network statistics of connectivity of linear point processes or Hawkes models (see section 5.1.6) to its function.…”
Section: Introductionmentioning
confidence: 99%